Novel Biomarkers for the diagnosis of diabetic nephropathy - Marcio Concepción-Zavaleta; Juan Quiroz-Aldave; Jacsel Suarez Rojas; José Paz-Ibarra; Pela Roseboom; Sofia Ildefonso-Najarro; Denis Cribilleros Zevallos; Francisca Zavaleta-Gutiérrez; Julia Coronado-Arroyo; Luis Concepción-Urteaga (Babol University of Medical Sciences, 2024)
Diabetes mellitus and its complications are a known public health problem nowadays. Diabetic nephropathy is one of the main complications and the result of multiple mechanisms, including: activation of the renin-angiotensin-aldosterone system, formation of advanced glycation end products and chronic inflammation that led to glomerular and tubulo-interstitial damage producing mesangial expansion and glomerulosclerosis, which finally results in chronic kidney disease. Early detection of diabetic nephropathyis essential for adequate intervention to stop, or at least sloww down its progression. Multiple markers have been described, not only the classic ones such as serum creatinine, urea, and albuminuria, but at this point also novel biomarkers such as neutrophil gelatinase-associated lipocalin, tumor necrosis factor 1 receptor and monocyte chemoattractant protein-1, among others. The aim of this article was to provide an update review of the role of biomarkers in the diagnosis of diabetic nephropathy.